Students’ Cognitive Attitude toward the Use of Direct Written Corrective Feedback in L2 Writing - Nur Sailah; Abdul Halim (IAIN KENDARI, 2021)
ABSTRACTThe purpose of this research was to analyse and investigate students’ cognitive attitude toward the use of direct written corrective feedback in L2 Writing. The participants of this study consist of 17 students from Senior High School in MAN 1 Konsel at X Agama who were selected based on their participated in the classroom in the learning process. The students were done to follow the learning process used direct written corrective feedback method from the researcher. The qualitative data were analyzed byobservation form video recorded and reflection from the students. The results of the research indicated that direct written corrective feedback led the students have positive attitude. The students felt happy, motivated, and perceive that this method is useful to apply in L2 Writing. Regardless of positivity, there were some students that showed negative cognition after applied direct written corrective feedback that given by teacher. This study implies that, the use ofdirect written corrective feedback that was given is really helped crossing out the students’ errors in spelling and writing the correct form near the errors in order to assist them to acquire correct English direct corrective feedback is the way the teacher provides the student with the correct form of the student’s mistake in writing.